Knowledge, attitudes and practices (KAP) about rabies prevention and control: a community survey in Tanzania. - Maganga Sambo; Tiziana Lembo; Sarah Cleaveland; Heather M Ferguson; Lwitiko Sikana; Cleophas Simon; Honorati Urassa; Katie Hampson (Public Library of Science (PLoS), 2014)
Despite being entirely preventable, canine rabies still kills 55,000 people/year in developing countries. Information about local beliefs and practices can identify knowledge gaps that may affect prevention practices and lead to unnecessary deaths.We investigated knowledge, attitudes and practices related to rabies and its prevention and control amongst a cross-section of households (n = 5,141) in urban and rural areas of central, southern and northern Tanzania. Over 17% of respondents owned domestic dogs (average of 2.3 dogs/household),>95% had heard about rabies, and>80% knew that rabies is transmitted through dog bites. People who (1) had greater education, (2) originated from areas with a history of rabies interventions, (3) had experienced exposure by a suspect rabid animal, (4) were male and (5) owned dogs were more likely to have greater knowledge about the disease. Around 80% of respondents would seek hospital treatment after a suspect bite, but only 5% were aware of the need for prompt wound cleansing after a bite. Although>65% of respondents knew of dog vaccination as a means to control rabies, only 51% vaccinated their dogs. Determinants of dog vaccination included (1) being a male-headed household, (2) presence of children, (3) low economic status, (4) residing in urban areas, (5) owning livestock, (6) originating from areas with rabies interventions and (7) having purchased a dog. The majority of dog-owning respondents were willing to contribute no more than US$0.31 towards veterinary services.We identified important knowledge gaps related to, and factors influencing the prevention and control of rabies in Tanzania. Increasing knowledge regarding wound washing, seeking post-exposure prophylaxis and the need to vaccinate dogs are likely to result in more effective prevention of rabies; however, greater engagement of the veterinary and medical sectors is also needed to ensure the availability of preventative services.